Japan Aging Issues, Long Term Care Insurance (LTCI) and The Migration of Indonesian Nurse to Enter Japan Labor Market - Iskandar, Kurniawaty (Journal of Strategic and Global Studies, 2020)
Japan Aging Population is a resultant of various problems in both micro and macro levels analysis. Long Term Care Insurance (LTCI) is a strategic policy of Japan Government for the purpose to take care their Aging so that saving Japan human resources in order to remain active in the public sector. This system is facilitating the institutionalization the domestic work of caring the elderly to a professional work which need a license. Since Japan young generation specially women not interested in this kind of work as known as 3K type of work (Kitsui, Kitanai, Kikken), Japan deregulation is open for foreign workers to enter Japan 3K sectors that are no longer in demand. This article discusses on how factors contribute on Japan Aging Issue, LCTI as Government strategy to institutionalized the domestic work usually doing by female and the challenges for Indonesian nurses who enter Japan domestic labor market. They enter with various barriers to status and standard for acceptance of foreign workers along with the strict immigration policy of Japanese government and patriarchy system as Japan social construct.